1973
DOI: 10.1021/jf60188a024
|View full text |Cite
|
Sign up to set email alerts
|

Free amino acids of Pakistani wheat varieties

Abstract: The fate of ethephon in the bovine is speculative. It is possible that the compound may decompose in the presence of rumen fluid, with the release of ethylene gas, dihydrogen phosphite, and chloride ions. This reaction is thought to occur in plant tissues (Technical Service Data Sheet, 1969). The rapid degradation of ethephon in rumen fluid may explain the presence of only 9.8% of the intact compound in urine. Since ethephon is not fat-soluble, its absence in milk at low feeding levels is not surprising. Base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Gln and Glu are abundant amino acids present in a free form in many different foods such as wheat ( , ), soybean (), almonds (), cocoa (), and coffee (). Hence, the Maillard reaction may contribute significantly to the formation of 2-Pyr levels in cooked and roasted foods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gln and Glu are abundant amino acids present in a free form in many different foods such as wheat ( , ), soybean (), almonds (), cocoa (), and coffee (). Hence, the Maillard reaction may contribute significantly to the formation of 2-Pyr levels in cooked and roasted foods.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the formation of corresponding vinylogous compounds in foods is not clear-cut (see Figure 1) and must be studied on a case-by-case basis, taking into account the availability of free amino acids and sugars in the raw agricultural commodity and thermal-processing conditions. Gln and Glu are abundant amino acids present in a free form in many different foods such as wheat (26,27), soybean (28), almonds (28), cocoa (29), and coffee (30). Hence, the Maillard reaction may contribute significantly to the formation of 2-Pyr levels in cooked and roasted foods.…”
Section: Discussionmentioning
confidence: 99%
“…Free amino acids in eight Pakistani wheat varieties differ both qualitatively and quantitatively according to Elahi [117]. Glutemic acids, aspartic acids, phenylalanine, cystine tyrosine, and valine are common to all varieties.…”
Section: Effect Of Heat Stress On Wheat Biochemistrymentioning
confidence: 99%
“…2−4 The formation of mutagenics and carcinogenics in pyrolysates of proteinaceous foods is a health concern in the fields of food processing, preservation, and safety, 5 implying the existence of a correlation between mutagenic activity and proteins in food that have undergone thermal treatment during processing. 6−8 Glutamic acid is present in free form in many different foods such as wheat, 1,9 soybean, 10 almond, 10 cocoa beans, 11 and coffee. 12 It has been reported that pyrolysates of glutamic acid show more potent mutagenicities in the Ames test.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Amino acids, from a nutritional standpoint, are perhaps the most important constituents of our daily diet . They are the central building blocks of proteins and have applications in the food, agricultural, cosmetics, and pharmaceutical industries, where pyrolysis is commonly used. The formation of mutagenics and carcinogenics in pyrolysates of proteinaceous foods is a health concern in the fields of food processing, preservation, and safety, implying the existence of a correlation between mutagenic activity and proteins in food that have undergone thermal treatment during processing. Glutamic acid is present in free form in many different foods such as wheat, , soybean, almond, cocoa beans, and coffee .…”
Section: Introductionmentioning
confidence: 99%